The Role Of The Community To Perform Self Isolation As A State Defense Form In The Era Of Covid-19 - Yana Sylvana; Tri Wahyudi, Slamet; Firmansyah, Yohanes (Jurnal Indonesia Sosial Sains, 2021)
Covid-19 is a very serious problem in 2020, claiming millions of lives. One issue is the rapid spread rate and the large number of infected groups without clinical symptoms and has the potential to become a source of spread for other people. One way to prevent the spread of covid-19 is disciplined awareness of conducting self-isolation for infected groups. This research discusses self-isolation awareness as a form of state defense during Covid-19. This research is a literature review study that uses 3 types of approaches to discuss social issues, namely status approach, conceptual approach, and case approach. The results of this study reveal that we are only urged to stop the spread of this virus, with government appeals, by participating in defending the country without taking up arms, we can fulfill our role as good citizens. As described above, State defense is adjusted to current community conditions, e.g. in the midst of the Covid-19 pandemic. At this time, state defense updating is not just staying at home, but still productive with our home system work as usual. The government has issued various policies, including studying at home, working from home, and praying at home. Following the government's recommendation is actually a form of state defense to defend the country as a form of our love for Indonesia